DETERMINATION OF Paracoccidioides brasiliensis RESERVAREA MAPPING THE MIGRATORY STORY OF 128 PATIENTS - Moreto, TC; Barrozo, LV; Bueno, RA; Moris, DV; Mendes, RP (Revista do Instituto Adolfo Lutz, 2009)
The long latency period observed between infection and clinical manifestations of disease makes it difficult to determine the fungal reservaria, i e, area where the patients were infected. The aim of this paper was to study the migratory profile of 128 paracoccidioidomycosis (PCM) patients assisted at Botucatu University Hospital, to determine the fungal reservaria. Interviews were carried out with 128 patients about their place of birth, municipality of residence at the disease onset, first, second and third municipalities in the rural area of the longest periods of residence during their entire lives. Using geoprocessing techniques, several maps were made: place of birth, place of the last residence, place of birth matching the last residence and, place of birth matching the longest and the last municipality of residence. Out of 128 patients, 101 (78.9%) were born in 58 municipalities in São Paulo State. All 128 patients lived in a municipality in this State at the time of disease onset, corresponding to 56 municipalities. Sixty five patients (50.8%) had the same place of birth and last residence, and 87 (68.0%) had spent more time at the same place of their last residence. Finally, 62 (48.4%) patients were born, had the longest and the last residence in 31 municipalities in São Paulo State. The migratory profile of our patients suggested as reservaria a geographic arrangement predominantly in the SW-NE direction, confirming previous studies based only on their municipality of residence at the disease onset.